Development of a portable fetal and maternal heart rate recorder for 24 hours - Ahmed F.; Alauddin M.; Ali M.; Zahedi E. (2023)
This paper focuses on developing an ambulatory system capable of monitoring the fetal heart rate (FHR) as well as recording the FHR and maternal heart Rate (MHR) for 24 hours by two-development work. The first is a microcontroller board which uses three electrodes, to sense the abdominal electrocardiogram (AECG) signals and then process the signal for monitoring FHR and recording the fetal and maternal RR intervals for 24 hours. The RR intervals are recorded inside the external memory of the board for downloading into a PC through an RS232 interface. The board accommodates of a PIC17C44 microcontroller chip, address interface, SRAMs, ADC circuit, amplifier circuit, power supply circuit, RS232 interface circuit and display interface circuit. The second development is the appropriate algorithms for extracting the heart rates from the AECG. The algorithms detect the maternal and fetal R waves by using their respective matched filters and adaptive thresholding schemes, whilst the maternal electrocardiogram (MECG) is subtracted by an appropriately scaled template obtained from an averaging process. Then the ambulatory system for monitoring the FHR and recording the RR intervals is constructed. The size of the recorder is 5 inches 4 inches. Post-processing software have also been developed on the PC to simultaneously display both heart rate traces. The real data from several patients have also been presented in this paper.